Validating the S-STEM among Malaysian Pre-University Students (Jurnal Pendidikan IPA Indonesia, 2020)
The purpose of this study is to validate the measure of student attitudes toward science, technology, engineering, and mathematics (S-STEM). This study used the cross-sectional design to employ translation and cultural adaptation as well as providing evidence of the reliability and validity of the S-STEM. The instrument was administered to 748 pre-university students in Penang, Malaysia. Data were analyzed using confirmatory factor analysis (CFA) with AMOS 19.0. Results support S-STEM as a three-factor multidimensional construct, namely attitude towards science, attitude towards technology/engineering, and attitude towards mathematics. All statistics such as factor loadings, average variance explained, construct reliability, evidence of discriminant validity, and goodnessof-fit indices were found to be at acceptable values. These positive results are significant because although the instrument has undergone numerous modifications, such as translation and others, the generalizability of the instrument is still preserved in pre-university Malaysian students. Counselors may administer the instrument to facilitate the choice of courses to enroll at university. The research may utilize the instrument to gather data in providing measures to improve students’ participation in learning STEM. The practical implications, as well as the methodological limitations of the present study, are discussed.